PELAKSANAAN PENEGAKAN HUKUM PEMBERANTASAN TINDAK PIDANA PEREDARAN NARKOTIKA DI WILAYAH HUKUM POLISI RESOR KOTA BARELANG BATAM - Agustino, Reza; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The more widespread development of narcotic crime in Indonesia is very alarming for the nation's next, and so is the province of North Sumatra, Batam city its special. Therefore, the government's efforts are essential to eradicate narcotic crime because, criminal offenses are transnational narcotics has been undertaken using the modus operandi is very high, sophisticated technology, supported by a vast network of organizations.